1977
DOI: 10.1111/j.1365-2125.1977.tb04522.x
|View full text |Cite
|
Sign up to set email alerts
|

Beclomethasone dipropionate aerosol in treatment of perennial and seasonal rhinitis: a review of five years' experience.

Abstract: 1. Five years' experience in the use of beclomethasone dipropionate aerosol (BDA) in the treatment of 315 patients with upper respiratory tract allergy is reviewed. 2. A total of 223 patients with perennial rhinitis was treated. In 23, where the nasal allergy had recurred after oral corticosteroid therapy for asthma was withdrawn, BDA was effective in 69% of cases. A similar success rate (68%) was recorded in 169 patients suffering from perennial allergic rhinitis alone, but a satisfactory response was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…We have confirmed our original findings in children with seasonal asthma and hay fever, and have reported our long-term experience in the treatment of perennial and seasonal asthma, and also allergic rhinitis (Brown & Storey, 1973Brown et al, 1977). (Brown, 1958).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…We have confirmed our original findings in children with seasonal asthma and hay fever, and have reported our long-term experience in the treatment of perennial and seasonal asthma, and also allergic rhinitis (Brown & Storey, 1973Brown et al, 1977). (Brown, 1958).…”
Section: Introductionsupporting
confidence: 75%
“…Oral corticosteroid therapy must have suppressed these allergic phenomena, which were unmasked on transfer to (Brown & Storey, 1977).…”
Section: Methods Oftransfermentioning
confidence: 99%
“…618,940,941 Evaluation of the histologic and macroscopic appearance of the nasal mucosa after administration of intranasal corticosteroids has shown no deleterious pathological changes from that after placebo or antihistamines. 618,942 In vitro and some in vivo studies have shown that benzalkonium chloride alone, and in 1 clinical study, a corticosteroid nasal spray containing benzalkonium chloride, can promote ciliary stasis and reduce mucociliary transport.…”
Section: Bonementioning
confidence: 98%
“…When GCS sprays were first introduced, there was considerable concern about the risk of mucosal atrophy, based on the experience with GCS treatment of the skin. However, extensive, long-term clinical experience and a number of biopsy studies (24,110,144) have not indicated that such a risk exists in the nose.…”
Section: Side-effects and Long-term Safetymentioning
confidence: 99%